Digital fist bumps: searching for datafication and digitalisation in everyday CrossFit coaching practice - Sandra Krugly; Jason Tucker (Frontiers Media S.A., 2024)
The research presented here explores the nuances of data collection and sharing via digital platforms in everyday CrossFit coaching practice. There is a growing body of work on data and digital platforms in CrossFit, though currently there is a lack of understanding of the role of coaches in these processes. Empirically grounding the digital fitness practices of CrossFit coaching is essential for our understanding of the sport, as well as to critically engage with the dominant socio-technical narratives of the digital fitness revolution: narratives that obscure the agency of coaches. This research foregrounds the coaches' agency and lived experiences, focusing on their everyday coaching practices around data and digital platforms. Six semi-structured in-depth interviews with CrossFit coaches in Sweden were undertaken in 2023. These focused on if, when, how and why they collect, or encourage their participants to collect, data on their training and share this via digital platforms. The findings reveal several different, though interrelated, areas where the CrossFit coaches can be seen as mediating between often competing narratives around data and digital platforms. These everyday practices include mediating between group vs. individual training, data collection and sharing vs. "moving well", CrossFit's methodology of quantification of fitness vs. the needs of the participants and navigating the techno-solutionist vs. reductionist narratives around digital fitness tracking.